Executive Remuneration in New Zealand and Australia - Do Current Laws, Regulations and Guidelines Ensure "Pay for Performance"? - Schoenemann, Andreas (Victoria University of Wellington Law Review, 2006)
This article undertakes an examination of the current corporate governance frameworks relating to the remuneration of executives, and particularly executive directors, of listed companies in New Zealand and Australia. The theoretical background of the article builds on agency theory and managerial power theory. On this basis, performance-related remuneration is identified as crucial in aligning the divergent interests of shareholders and executives. Theories also suggest that the board of directors alone is not a sufficient mechanism to ensure that performance-related pay is implemented in practice. Examination of substantive remuneration rules regarding the structure and form of remuneration agreements finds that in both New Zealand and Australia the relevant problems are only sparsely addressed in enforceable law. More emphasis is put on procedural remuneration rules. Particularly in the fields of disclosure and shareholder involvement, Australia is a step ahead of New Zealand.